The Influence of Leadership Style and Work Stress on Employee Performance in the Product Creation Center of PT Adis Dimension Footwear, Tangerang Regency - Septiana, Aditya Bagus; Setiawan, Temmy; Azhari, Muhammad Zakky (IJOSPOL - International Journal of Social, Policy and Law, 2026)
Leadership style and work stress are one of the factors that cause optimal or not optimal employee work. On the other hand, organizations need a good leadership style and minimize work stress in employees, both of which aim to improve employee performance. The purpose of this study was to determine the extent of influence of leadership style and work stress on the work productivity of employees in the Product Creation Center at PT Adis Dimension Footwear, Tangerang Regency. This study uses a quantitative descriptive method, namely research that describes variables as they are supported by data in the form of numbers generated from actual conditions. The population in this study were all employees in the Product Creation Center at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 73 respondents. The technique used to determine the sample in this study was the simple random sampling technique. The results of this study indicate that (1) partially, leadership style significantly influences the work productivity of employees in the Product Creation Center section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (5.894 > 1.994) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (2) Partially, work stress significantly influences the work productivity of employees in the Product Creation Center section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (4.112 > 1.994) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, leadership style and work environment significantly influence the work productivity of employees in the Product Creation Center section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount> Ftable (101.795>3.13) with a significance level of 0.000, thus Ha is accepted and H0 is rejected. Based on the results of the study, it can be concluded that the variables of leadership style and work stress, both partially and simultaneously, have a significant influence on the work productivity of employees in the Product Creation Center section at PT Adis Dimension Footwear, Tangerang Regency.